A report on the practice in industry training in fish preservation. - Mission, Helen A. (College of Fisheries, University of the Philippines, 1970)
Although the making of this report was essentially directed towards fulfilling a course requirement in "practice-in-industry", the author has found consideration, merely secondary. For after four months completion of the work, the author is tremendously benefited not only with working techniques and skills that go with the report making, but also a valuable knowledge of our country's unheralded past. At the very start of endeavour, the task seemingly difficult and discouraging calls for zealousness and patience. Gradually, however the excitement to results of painstaking effort, time and material considerations in the research work became overwhelming and interest profoundly developed. The subject of this report was based on our experiments as to the effect of antibiotic on the keeping quality of fresh fish. The process, with which the author had undertaken actual work applying the techniques in icing and daily observation after examination of samples. To this after a time of conducting such work, it is a convincing knowledge that the use of antibiotic greatly assists in extending the keeping quality of fresh fish.